Gibler
Gibler
04-07-2014
Mathematics
contestada
let f(x)=2x-3 and g(x)= -x^2-1 find ( g o f) (x)
Respuesta :
konrad509
konrad509
04-07-2014
[tex]g \circ f=-(2x-3)^2-1=-(4x^2-12x+9)-1=\\ =-4x^2+12x-9-1=-4x^2+12x-10\\[/tex]
Answer Link
kate200468
kate200468
04-07-2014
[tex]f(x)=2x-3\ \ \ and\ \ \ g(x)= -x^2-1\\\\( g \circ f) (x)=g\bigg(f(x)\bigg)=g\bigg(2x-3\bigg)=-(2x-3)^2-1=\\\\=-(4x^2-12x+9)-1=-4x^2+12x-9-1=-4x^2+12x-10[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 35+ )
Otras preguntas
14.849 rounded to the nearest hundredth is
Consider this statement, which survey respondents are asked to agree or disagree with: Government should play a major role in helping families that, through no
What type of proof explains the solution to a problem through a series of sentences?
n+4-9-5n combine like terms
Find the LCM of 10 and 16.
What is life? What is our purpose?
Are you not wittein exam today
Uli correctly combined all like terms in the expression 5 x + 6 minus 4 y minus 3 + 3 x minus 2 to write an equivalent expression. What is the coefficient for t
What is the biggest challenge facing entrepreneurs who start small businesses?
American Indians were seen as “uncivilized,” so the Spanish tried to ____ them.